Analgesic effect of intra-articular ropivacaine injection after arthroscopic surgery on the shoulder joint in dogs - J.H. Kim; S.H. Seok; T.Y. Park; H.J. Kim; J.M. Kim; S.W. Lee; H.C. Lee; S.C. Yeon (Veterinární Medicína, 2018)
Shoulder joint disorders are a major cause of forelimb lameness in dogs, and osteochondrosis, degenerative joint disease, and bicipital tenosynovitis are common joint disorders that have been reported in dogs. Many studies have investigated pain management after arthroscopy in human medicine, but reports from veterinary medicine are rare. Ropivacaine is a new amide local anaesthetic drug and a single isomer drug that is used more widely than bupivacaine in human medicine because it has fewer side effects. The present study was conducted to evaluate the analgesic effect of intra-articular injection of ropivacaine after arthroscopic surgery in dog shoulder joints. To accomplish this, ten dogs were randomly divided into two groups of five who underwent the same anaesthesia protocol and shoulder arthroscopic examination. After shoulder arthroscopy, ropivacaine or 0.9% NaCl was injected into the shoulder joint cavity and the dogs were evaluated at one hour, two hours, four hours, six hours, 12 hours and 24 hours after surgery. The evaluated parameters were heart rate, respiratory rate, lameness score, visual analogue scale and the short form of the Glasgow composite measure pain scale. Ropivacaine showed a higher analgesic effect than 0.9% NaCl, indicating that it may be useful for pain management following arthroscopic surgery in dogs.